Prognostic significance of primary tumour volume in nasopharyngeal carcinoma – a single institute study - S.D. Shamsundar; Jagannath K.P.; Niveditha S.; Aradhana K.; R. Nanda; B. Thejaswini (International Journal of Medical Research and Review, 2019)
Introduction: Nasopharyngeal carcinoma is very uncommon in the southern part of India, the age-adjusted incidence rate is less than 1 per 1,00,000 population. This study is undertaken to evaluate the outcome of nasopharyngeal carcinoma and its correlation with Primary tumor volume.Material and methods: Total of 50 non-metastatic nasopharyngeal carcinoma patients treated with concurrent chemo radiation between January 2013 and December 2015 were included in the study. All patients were treated via IMRT with dose of 66-70Gy, along with concurrent chemotherapy. Initial tumour volume was measured from CT based contouring and mean dose delivered was calculated. All patients were followed up for survival, relapse and metastasis.Results: The median follow up for the group was 24 months. The median Gross tumor volume of primary disease and nodal disease was 61.6 cubic centimetres and 35.4 cubic centimeters respectively. The 2 year Disease free survival and Overall survival for the entire group was 64% and 68% respectively. There was significant difference (p-0.018) between disease free survival of low volume disease group (LVD) which was 78 % as compared to high volume disease (HVD) group 52 % at 24 months, similarly Overall survival was also significantly better (p-0.015) in LVD group as compared to HVD group 80% vs 55% at 24 months. Among the treatment related factors adjuvant chemotherapy significantly improved the outcome in HVD group but no difference was seen in LVD group.Conclusion: Our patients had large volume primary disease, the OS and DFS was significantly better in LVD patients, adjuvant chemotherapy after concurrent chemoradiotherapy had no additional benefit for LVD patients but improved DFS and MFS in HVD Patients.